Cubosomes; An Approach to Sustain and Improve the Ocular Delivery for Glaucoma Treatment: Box Benhken Optimization, Formulation, In Vitro Characterization and Ex Vivo Permeation Study - Aher, Shubhangi; Nimase, Bharati (Journal for Research in Applied Sciences and Biotechnology, 2024)
Introduction: In glaucoma, acetazolamide (ACZ) is used to lower intraocular pressure (IOP). Low aqueous solubility and decreased corneal permeation are two characteristics of ACZ. This research intends to enhance the ocular delivery of ACZ. Materials and Methods: Using a Box-Behnken design, cubosomes loaded with acetazolamide were made using the Melt dispersion emulsification and sonication method. The independent variables included Glyceryl monoolein (GMO), polyvinyl alcohol (PVA) and Poloxamer 407 (P407. The prepared formulations underwent evaluation for polydispersity index (PDI), particle size and entrapment efficiency. Thermal analysis, in vitro characterisation and permeation were among the additional tests performed on the developed formulation. Results: Optimized formulation showed PDI of 0.23 ± 0.03, mean particle size of 243 ± 4.2 nm, zeta potential of -26.1 ± 0.6 mV, entrapment efficiency of 73.99% and cubic structure under TEM. Drug penetration through goat cornea has increased, according to an ex vivo permeation study. The prepared cubosome safety, stability and ability to be delivered through the cornea were confirmed by the ocular irritation test. Conclusion: The optimized cubosomal formulation has the potential to improve glaucoma treatment and be regarded as promising for ocular delivery of ACZ.